Crop diversification strategies for yield enhancement in finger millet-based cropping systems - Shilpa,; Lalitha, B. S.; Nagaraj, K. H.; Murthy, K. N. Kalyana; Jayadeva, H. M.; Sannagoudar, Manjanagouda S.; Vasundhara, R.; Amrutha, T. G.; Nagangoudar, Mahantesh B.; Raddy, Gurunath; Salmankhan, R. M.; Kavyashree, C.; et al. (Frontiers in Agronomy, 2025)
Indian agriculture is confronted with a multitude of sustainability challenges, including the impacts of climate change, inefficiencies in input usage, depletion of natural resources, soil degradation, excessive energy consumption, and various environmental concerns viz., burning of the crop residues. Tackling these challenges necessitates integrated strategies that foster climate-resilient farming, optimize resource utilization, and encourage the adoption of sustainable agricultural practices. To address these issues, a field study was conducted focusing on millet + legume combination, wherein soybean, green gram and black gram were intercropped with finger millet, and cowpea was grown as sequence crop. The Randomized Complete Block Design with Factorial concept with three replications was employed to assess the effectiveness of different finger millet-based legume intercropping systems and varied levels of recommended doses of fertilizers (RDF) to intercrops. The findings revealed that, among the different intercropping systems, the combination of finger millet + green gram recorded significantly higher (p=0.05) grain (2513.10 kg/ha) and straw (7526.19 kg/ha) yield of finger millet The same intercropping system yielded significantly (p=0.05) higher seed (899.40 kg/ha) and haulm yield (2295.12 kg/ha) of green gram compared to other intercrops. Among the nutrient management approaches, applying 75% RDF to the component crops resulted in the highest grain/seed yield (2688.98 kg/ha for finger millet and 932.46 kg/ha for green gram) and straw/haulm yield (7850.88 kg/ha for finger millet and 2122.74 kg/ha for green gram). The residual impact of the finger millet-based intercropping system on a subsequent cowpea crop led to a notable increase in its seed yield (1599.66 kg/ha) and haulm yield (3445 kg/ha) under finger millet + soybean intercropping system, where 75% RDF was supplied to soybean. Additionally, productivity metrics such as finger millet equivalent yield (FMEY), land-equivalent ratio (LER), competition ratio (CR), and area-time equivalent ratio (ATER) were maximized in the finger millet + green gram intercropping system. These findings underscore that the combination of green gram with finger millet, along with the application of 75% RDF, significantly (p=0.05) boosts the overall productivity of the intercropping system.